Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/eve.13236
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic features associated with the lumbosacral or lumbar 5–6 symphyses in 64 horses with lumbosacral‐sacroiliac joint region pain (2012–2018)

Abstract: 23.1%) had congenital fusion of either joint. Limitations include the lack of age-matched control horses. However, the purpose of the study was to raise awareness of lesions of the L5-6 and lumbosacral symphyses, which may contribute to pain and poor performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 35 publications
5
37
0
Order By: Relevance
“…The test performed by the riders was purpose-designed to include 10 m diameter circles because it has previously been observed that this movement can influence both lameness and behaviour [ 6 ]. This study also reinforces the importance of evaluating the quality of canter, which may be compromised especially in association with hindlimb lameness or sacroiliac joint region pain [ 17 , 30 , 31 , 32 ]. Although gait abnormalities in canter were not significant in the final model, it does not mean that such abnormalities are not of biological significance.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The test performed by the riders was purpose-designed to include 10 m diameter circles because it has previously been observed that this movement can influence both lameness and behaviour [ 6 ]. This study also reinforces the importance of evaluating the quality of canter, which may be compromised especially in association with hindlimb lameness or sacroiliac joint region pain [ 17 , 30 , 31 , 32 ]. Although gait abnormalities in canter were not significant in the final model, it does not mean that such abnormalities are not of biological significance.…”
Section: Discussionsupporting
confidence: 72%
“…Throughout the test the gait was assessed subjectively by an experienced lameness diagnostician, used to evaluating ridden horses. The presence of forelimb lameness, hindlimb lameness or lack of hindlimb impulsion and engagement, or an abnormal canter (a stiff and stilted canter, close spatial and/or temporal placement of the hindlimbs, a canter which lacked a suspension phase [ 15 , 16 ], or exaggerated lifting of the forehand during canter, associated with abnormally wide spatial separation of the hindlimbs [ 17 ]) was recorded. Lameness was graded on a 0–8 scale [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Lumbosacroiliac pain in horses is a common cause of poor performance and lack of power in the hindlimbs (Jeffcott et al 1985;Denoix 1998;Dyson 2010;Peters 2012;Barstow and Dyson 2015;Boado et al 2020). As in humans (Dansie and Turk 2013) objective assessment of low back and pelvic pain, and clear identification of its cause(s) are not easy in horses Denoix and Dyson 2010;Dyson 2010;Haussler 2010;Denoix 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Intervertebral disc disease could be an incidental finding since it has been observed in clinically normal horses 24,25 . However, in some cases it could be clinically relevant as a cause of nerve root pain, extradural compressive myelopathy, and more uncommonly fibrocartilaginous embolism, or both 17,24,26,27 …”
Section: Discussionmentioning
confidence: 99%
“…24,25 However, in some cases it could be clinically relevant as a cause of nerve root pain, extradural compressive myelopathy, and more uncommonly fibrocartilaginous embolism, or both. 17,24,26,27 Characterization of pelvic fractures is essential for determination of prognosis. 28 Ultrasonographic evaluation of the pelvis includes the coxofemoral joints, sacroiliac joints, and pubic symphysis and can be performed SC and transrectally in the standing horse.…”
Section: Definitive Diagnosismentioning
confidence: 99%